Soil cover shapes organic matter pools and microbial communities in soils of maritime Antarctica - Victoria Martin (Centre for Microbiology and Environmental Systems Science, University of Vienna); Hannes Schmidt (Centre for Microbiology and Environmental Systems Science, University of Vienna); Alberto Canarini (Centre for Microbiology and Environmental Systems Science, University of Vienna); Marianne Koranda (Centre for Microbiology and Environmental Systems Science, University of Vienna); Bela Hausmann (Joint Microbiome Facility of the Medical University of Vienna and the University of Vienna); Carsten W. Müller (Technical University of Berlin, Institute of Ecology); Andreas Richter (Centre for Microbiology and Environmental Systems Science, University of Vienna) (Geoderma, 2024)
The abstract is available here: https://uscholar.univie.ac.at/o:2086271 The abstract is available here: https://uscholar.univie.ac.at/o:2086271